Postgraduate nursing students' expectations of their supervisors in Iran: A qualitative study - Fatemeh Hajihosseini; Mansoureh Zagheri Tafreshi; Meimanat Hosseini; Ahmad Reza Baghestani (Wolters Kluwer Medknow Publications, 2018)
Background: Exploring the expectations of postgraduate nursing students from their supervisors is required in order to meet the expectations, raise the general students' satisfaction, and enhance the students' capabilities to the highest degree possible. The present study was conducted to explore the expectations of postgraduate nursing students from their supervisors. Materials and Methods: This qualitative study was done through semi-structured individual interviews with seven PhD students and 14 master's students in two focus groups from three universities in Tehran, Iran. The data were analyzed using the inductive approach and through conventional content analysis. Results: The analysis of the data led to the extraction of five categories (support for the students, good communication skills, professional competence, guiding the students, and professionalism) within 12 subcategories. Conclusions: The results revealed that postgraduate students expect their supervisors not only to guide and support them in education and research but also have good communication skills, be professional, and value professionalism. Therefore, supervisors should try to meet these expectations and offer practical strategies for better realization of their needs.